Application of the extended H∞ Filter for attitude determination and gyro calibration - Silva, William R.; Kuga, Hélio K.; Zanardi, Maria C. [UNESP] (My University, 2014)
This work describes the attitude determination and the gyros drift estimation using the Extended H∞ Filter for nonlinear systems. Such filter uses the Taylor series to approximate the non-linearity of the known dynamics and assumes that the noise sources have approximately known statistical properties. The application uses measurement data of a real satellite CBERS-2 (China Brazil Earth Resources Satellite 2) which has polar sun-synchronous orbit with an altitude of 778km, crossing Equator at 10:30am in descending direction, frozen eccentricity and perigee at 90 degrees, and provides global coverage of the world every 26 days. Herein one proposes to use an extension of the H∞linear filter for the nonlinear case of attitude estimation with nonlinearity in both the dynamics and the measurement model. The aim is to highlight and magnify the properties of the H∞filter in terms of its favourable characteristics. Actually, the so named extended H∞filter provides a rigorous method for dealing with systems that have model and noise uncertainties. The derivation and customization of the filter to this specific application (attitude determination) are described together with details of implementation. Besides, one preferred to use real measured DSS (Digital Solar Sensor), IRES (Infrared Earth Sensor), and gyro data to assess the procedure in a real application. The results in this work show that one can reach accuracies in attitude determination within the prescribed requirements, besides providing estimates of the gyro drifts which can be further used to enhance the gyro error model.